2001
DOI: 10.3102/00028312038001143
|View full text |Cite
|
Sign up to set email alerts
|

Principled Moral Reasoning and Behavior of Preservice Teacher Education Students

Abstract: Although teachers have considerable influence on young people’s moral development, results of several studies suggest that preservice education students demonstrate lower principled moral reasoning than college students with other majors. The purpose of this study was to measure the levels of principled moral reasoning of preservice teacher education students and to compare their performance with that of college students with other majors. The study also investigated the relationship between the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 18 publications
(27 reference statements)
12
81
1
Order By: Relevance
“…Specifically, advanced moral reasoners are less likely to focus exclusively on self-interest when making decisions and are more inclined to emphasize abstract notions such as ''fairness'' and the ''greater good''. On a conceptual level, then, advanced moral reasoners should be less likely than others to seek personal advantage by cheating, and some empirical evidence supports this possibility (Cummings et al, 2001;Leming, 1978;Malinowski and Smith, 1985; for less supportive evidence, however, see Bernardi et al, 2004;Bruggeman and Hart, 1996;West et al, 2004).…”
Section: Ethics Instruction and Cheating Behaviorsmentioning
confidence: 92%
“…Specifically, advanced moral reasoners are less likely to focus exclusively on self-interest when making decisions and are more inclined to emphasize abstract notions such as ''fairness'' and the ''greater good''. On a conceptual level, then, advanced moral reasoners should be less likely than others to seek personal advantage by cheating, and some empirical evidence supports this possibility (Cummings et al, 2001;Leming, 1978;Malinowski and Smith, 1985; for less supportive evidence, however, see Bernardi et al, 2004;Bruggeman and Hart, 1996;West et al, 2004).…”
Section: Ethics Instruction and Cheating Behaviorsmentioning
confidence: 92%
“…Teachers who have higher levels of moral development and awareness generate better academic outcomes for students (Chang, 1994;Cummings, Dyas, Maddux, & Kochman, 2001). On the other hand, teachers with lower levels of moral development teach students less effectively and demonstrate inappropriate behaviours (Reiman & Peace, 2002;ThiesSprinthall, 1984).…”
Section: Teaching: a Morals And Value-based Processmentioning
confidence: 99%
“…Teachers therefore should be able to make sound moral judgements and look beyond their own personal interests to the broader moral dimension that presents itself in their classrooms. Teachers who reason at the postconventional or principled levels of moral reasoning are more likely than those who reason at lower levels to have a heightened sense of their moral responsibility as well as the moral dimension of teaching (Chang 1994;Cummings et al 2001;Cummings et al 2010).…”
Section: The Moral Role Of the Teachermentioning
confidence: 99%
“…Furthermore, it is suggested that the tools needed to teach social responsibility and social change must be embedded in pre-service teacher education (Cochran-Smith 1999, 138). Many prior studies examining the moral reasoning of teacher education students have found that they function at the conventional level of moral reasoning (Chang 1994;Lampe 1994;McNeel 1994;Cummings et al 2001Cummings et al , 2007.…”
Section: The Moral Role Of the Teachermentioning
confidence: 99%